Optimisation of N application for a maize crop grown in a shallow, irrigated soil - Diez, J.A.=700 1 Tarquis, A.; Cartagena, M.C.; Vallejo, A.
(Es, En)
ilus., 33 ref.
Keywords: NITROGENO; DOSIS DE APLICACION; CULTIVO; MAIZ; RIEGO; SUELOS CULTIVABLES; ESPAÑA; BALANCE DE NITROGENO; SUELO PETROCALCICO